Homoeopathy in Parasitic Skin Infestations with Special References to Scabies (Homoeopathy for All, 2026)
Scabies is a parasitic infestation , not a bacterial or viral infection, caused by mites that burrow into the skin. It is highly contagious and spreads through close, skin to skin contact, it occurs world wide but it is most common in low income tropical areas. Children and older people in resource poor areas are at higher risk. Globally it is estimate to affect more than 200 million people at any time and more than 400 million people cumulatively every year. This articles shows an overview about scabies infection with cause, clinical features and types with general & homoeopathic management .
Keywords: Scabies; parasitic infection; itching; mites; Homoeopathy